Strategi Pemasaran Untuk Meningkatkan Penjualan UMKM Tas Zamano Di Kebonharjo - Dina Kharisma; Nining Hidayah; Mohammad Iqbal (Magister Manajemen STIE Bank BPD Jateng, 2023)
UMKM are one of the important pillars in the national economic sector. UMKM need to be pushed back after the Covid-19 pandemic. One of the things that can be done to encourage the rise of UMKM is by digitizing marketing and product innovation. This study aims to determine the factors that decreased sales and marketing strategies that were implemented, how to deal with the obstacles that occurred, weaknesses and obstacles in Zamato bags. This study used descriptive analysis, interview and observation data collection techniques, and purposive sampling technique. There are 5 samples in this study (respondents) who are business owners, consumers, employees, and the research team